The effect of US uncertainty shock on international equity markets: The role of the global financial cycle - Afees A. Salisu; Rangan Gupta; Idris A. Adediran (Review of Economic Analysis (REA), 2023)
We contribute to the literature on the international propagation of uncertainty shocks with a Global Vector Autoregressive (GVAR) model that quantifies the spillover effects of uncertainty shocks in the US on to real equity prices of 32 advanced and emerging countries (besides the US). In this regard, we also account for the role of global financial market conditions in the propagation of these shocks, using high and low values of the Global Financial Cycle (GFCy) index. Using quarterly data over 1980:1 to 2019:2, our findings reveal greater response of advanced markets than emerging counterparts to an US uncertainty shock. Further, we show consistent higher negative responses during weak financial conditions than otherwise, confirming the intervening role of the GFCy index. Our results have important implications for investors and policymakers.
Keywords: C32; G15; 330; Uncertainty Shocks; International Financial Markets; Global Vector Autoregressive Model